Explore BrainMass
Share

Explore BrainMass

    Real number proofs

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    -(-a)=a

    -(a)*-(b)=a*b

    if a doesn't equal 0 then 1/a doesn't equal 0

    if a doesn't equal 0 then (-1)/a = 1/(-a)

    a(b-c)=ab-ac

    © BrainMass Inc. brainmass.com October 9, 2019, 10:23 pm ad1c9bdddf
    https://brainmass.com/math/discrete-math/real-number-proofs-218794

    Solution Preview

    Proof:
    1. Since a + (-a) = 0, then we subtract (-a) on both sides and get
    a = 0 - (-a).
    So we get -(-a) = a
    2. Since -(a) = (-a), then we use the result in 1 and get
    -(a) * -(b) = (-a) * -(b) = -(-a) * b = a * b
    ...

    Solution Summary

    This provides examples of proving several properties of real numbers.

    $2.19